2022
DOI: 10.3390/app13010570
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Connected Solar Photovoltaic System for Nile Tilapia Farms in Southern Mexico: Techno-Economic and Environmental Evaluation

Abstract: Tilapia farming is the predominant aquaculture activity, with 4623 aquaculture farms in Mexico alone. It is relevant to apply technological alternatives to mitigate production costs, mainly those associated with supporting energy savings for aeration and water pumping in aquaculture farms. There is limited information confirming the feasibility of implementing photovoltaic systems connected to the grid (On grid-PV) in aquaculture farms. The working hypothesis proposed for the development of the work was that O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…ALCS refers to the normalised nominal annual savings with the same lifespan and net present value as the actual project [23] [24]. It is calculated by considering NPV, discount rate, and project lifespan:…”
Section: ( )mentioning
confidence: 99%
“…ALCS refers to the normalised nominal annual savings with the same lifespan and net present value as the actual project [23] [24]. It is calculated by considering NPV, discount rate, and project lifespan:…”
Section: ( )mentioning
confidence: 99%
“…It could also be concluded that it was very convenient to invest in solar PV system technology in Zakho city, Iraq. Delfín‐Portela et al [ 23 ] designed grid‐connected PV systems for rural Tilapia farms and evaluated their technical, economic, and environmental feasibility. The grid‐connected PV design was carried out at an aquaculture farm in the Mexican state of Veracruz.…”
Section: Introductionmentioning
confidence: 99%